Negative electrode sheet and preparation method thereof, secondary battery, battery module, battery pack and power-consuming device
By setting a graphite layer structure with specific OI values and thickness on the negative electrode sheet of the lithium-ion battery, the problem of high rebound rate of the negative electrode sheet is solved, the service life and safety performance of the battery are improved, and the rate performance is maintained.
Patent Information
- Application Number
- CN202210414297.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-04-20
AI Technical Summary
The rebound rate of the negative electrode plate of existing lithium-ion secondary batteries is too high, resulting in excessive expansion force of the battery, diaphragm extrusion, and poor electrolyte infiltration, which in turn accelerates capacity attenuation and shortens service life, while increasing safety risks.
Using a negative electrode sheet including a first graphite layer, a lithium titanate layer and a second graphite layer, a first graphite layer with a higher OI value, a lithium titanate layer and a lower one are provided on the current collector surface. The second graphite layer of OI value is adjusted to adjust the OI value and thickness of the graphite layer to reduce the rebound caused by volume changes.
It effectively reduces the rebound rate of the negative electrode plate, extends the service life of lithium-ion batteries, improves safety performance, and ensures the battery's rate performance and reduces capacity attenuation.
Smart Images

Figure CN115810717B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode sheet for a secondary battery, a method for preparing the negative electrode sheet, and a secondary battery, a battery module, a battery pack and an electrical device comprising the negative electrode sheet. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] In the prior art, graphite is usually used as the active material of the negative electrode plate of lithium-ion secondary batteries. However, in the manufacturing and use of lithium-ion secondary batteries in the prior art, the rebound rate of the negative electrode plate is too high, which makes the expansion force of the lithium-ion battery too large, the diaphragm is squeezed, the electrolyte is poorly infiltrated, and the polarization increases. This leads to accelerated capacity decay and shortened service life of the lithium-ion battery. On the other hand, the excessive rebound rate of the negative electrode plate can also cause the plate corner to break, increasing the safety risk of the lithium-ion battery.
[0004] Therefore, there is an urgent need in the prior art for a negative electrode sheet with a reduced rebound rate, thereby improving the service life and safety performance of lithium-ion batteries. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present application is to provide a negative electrode plate with a low rebound rate, so as to improve the service life and safety performance of the lithium-ion battery using the negative electrode plate, while ensuring the battery's rate performance and reducing the battery's capacity attenuation.
[0006] In order to achieve the above object, in one aspect, the present application provides a negative electrode sheet, which includes a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer includes:
[0007] First graphite layer;
[0008] a lithium titanate layer; and
[0009] The second graphite layer,
[0010] The first graphite layer is disposed on at least one surface of the current collector, the lithium titanate layer is disposed on the surface of the first graphite layer, and the second graphite layer is disposed on the surface of the lithium titanate layer.
[0011] The OI value of the first graphite layer is greater than or equal to 20.0, and may be 30.0 to 40.0. The OI value of the second graphite layer is less than or equal to 15.0, and may be 8.0 to 12.0.
[0012] Therefore, by setting a lithium titanate layer in the active material layer, the rebound caused by volume change in the manufacturing process and the battery charging and discharging process of the negative electrode plate is effectively reduced, thereby greatly improving the service life and safety performance of the lithium-ion battery. By setting a first graphite layer with a higher OI value between the lithium titanate layer and the current collector layer, the problem of rate performance degradation caused by low electronic conductivity of lithium titanate is solved. By setting a second graphite layer with a lower OI value on the surface of the lithium titanate layer, the densification degree of the SEI film on the surface of the active material layer is improved, the consumption of active lithium ions is delayed, and the capacity decay of the battery is reduced.
[0013] In any embodiment, the thickness of the first graphite layer is less than or equal to 100 μm.
[0014] Thereby, it can be ensured that the first graphite layer has an OI value within the above-mentioned specific range, and at the same time, the adverse effect of the volume change of graphite on the rebound characteristics of the negative electrode plate during the manufacture and use of the lithium-ion battery can be minimized.
[0015] In any embodiment, the thickness of the lithium titanate layer is 25 to 50 μm.
[0016] In this way, the role of the lithium titanate layer in reducing the rebound of the negative electrode plate can be fully utilized, while maintaining the rate performance of the lithium-ion battery.
[0017] In any embodiment, the thickness of the second graphite layer is less than or equal to 100 μm.
[0018] Thereby, it is possible to ensure that the second graphite layer has an OI value within the above-mentioned specific range, and at the same time, minimize the adverse effects of the volume change of graphite on the rebound characteristics of the negative electrode plate during the manufacture and use of lithium-ion batteries.
[0019] In any embodiment, the thickness of the active material layer is 50 to 150 μm.
[0020] Therefore, the negative electrode sheet can have good wettability while ensuring the energy density of the negative electrode sheet.
[0021] In any embodiment, the compaction density of the negative electrode sheet is 0.9 to 1.8 g / cm 3 .
[0022] In this way, the energy density of the lithium-ion battery can be ensured, and at the same time, the rebound rate of the negative electrode plate can be further reduced, thereby ensuring the safety performance, rate performance and cycle performance of the battery.
[0023] In a second aspect, the present application provides a method for preparing a negative electrode sheet, comprising:
[0024] providing a current collector;
[0025] forming a first graphite layer including a first graphite on at least one surface of the current collector;
[0026] forming a lithium titanate layer including lithium titanate on a surface of the first graphite layer;
[0027] forming a second graphite layer including a second graphite on the surface of the lithium titanate layer to obtain a laminate having an active material layer on at least one surface of the current collector, the active material layer including the first graphite layer, the lithium titanate layer and the second graphite layer;
[0028] Cold pressing the laminate to obtain a negative electrode sheet;
[0029] The OI value of the first graphite is greater than 2.0 and less than or equal to 6.0, and may be selected as 3.0 to 5.0; the OI value of the second graphite is greater than or equal to 0.5 and less than 2.0, and may be selected as 1.0 to 1.5.
[0030] Therefore, it can be ensured that after the negative electrode plate is cold pressed, the first graphite layer and the second graphite layer respectively have OI values within the above-mentioned specific range.
[0031] In any embodiment, the cold pressing pressure is 15 to 70T.
[0032] In this way, the energy density of the negative electrode plate can be controlled, and at the same time, the safety hazard caused by the particles in the active material layer breaking during the pressing process can be avoided.
[0033] In any embodiment, after the stack is cold pressed, the OI value of the first graphite layer formed is greater than or equal to 20.0, and may be 30.0-40.0, and the OI value of the second graphite layer formed is less than or equal to 15.0, and may be 8.0-12.0.
[0034] Therefore, as described above, by ensuring that the first graphite layer and the second graphite layer respectively have OI values within the above-mentioned specific range, the rate performance of the lithium-ion battery using the negative electrode plate can be fully guaranteed while reducing the capacity attenuation of the lithium-ion battery.
[0035] In any embodiment, after the stack is cold pressed, the compaction density of the negative electrode sheet formed is 0.9 to 1.8 g / cm 3 .
[0036] Therefore, as described above, by ensuring that the negative electrode plate has a compaction density within the above range, the capacity of the lithium-ion battery using the negative electrode plate can be fully guaranteed, while ensuring the wettability of the plate during the preparation process and the production efficiency of the plate.
[0037] In a third aspect, the present application provides a secondary battery, comprising:
[0038] Positive electrode;
[0039] The negative electrode sheet of the first aspect of the present application, or the negative electrode sheet prepared according to the preparation method of the second aspect of the present application;
[0040] Electrolytes; and
[0041] Diaphragm.
[0042] As described above, the service life and safety performance of the secondary battery of the present application are improved, while the rate performance is fully guaranteed and the capacity attenuation is reduced.
[0043] In a fourth aspect, the present application provides a battery module, which includes the secondary battery of the third aspect of the present application.
[0044] In a fifth aspect, the present application provides a battery pack comprising the battery module of the fourth aspect of the present application.
[0045] In a sixth aspect, the present application provides an electrical device, which includes the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, or the battery pack of the fifth aspect of the present application.
[0046] In the negative electrode plate of the present application, by providing an active material layer including a first graphite layer with a specific OI value, a lithium titanate layer and a second graphite layer with a specific OI value on the current collector, the rebound of the negative electrode plate caused by volume change during the manufacturing process and the battery charging and discharging process can be effectively reduced, thereby improving the service life and safety performance of the lithium-ion battery, while fully ensuring the battery's rate performance and reducing the battery's capacity attenuation. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Schematic diagram of a negative electrode sheet having an active material layer on one surface of a current collector according to an embodiment of the present application.
[0048] Figure 2 It is a trend chart of the rebound rate change of the negative electrode sheets in Example 1, Control Examples 1-2 and Comparative Examples 1-2.
[0049] Figure 3a It is a curve diagram showing the expansion force of the lithium ion batteries in Example 1, Control Examples 1-2 and Comparative Examples 1-2 changing with the number of cycles.
[0050] Figure 3b It is a graph showing the capacity retention rate of the lithium ion batteries in Example 1, Control Examples 1-2 and Comparative Examples 1-2 as a function of the number of cycles.
[0051] Figure 4a It is a graph showing the capacity retention rate of the lithium ion batteries in Example 2 and Comparative Examples 3-4 as a function of the number of cycles.
[0052] Figure 4b It is a bar graph of the rate capacity retention ratio of the lithium ion batteries in Example 2 and Comparative Examples 3 and 4.
[0053] Figure 5 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0054] Figure 6 yes Figure 5 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0055] Figure 7 is a schematic diagram of a battery module according to an embodiment of the present application.
[0056] Figure 8 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0057] Fig. 9 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0058] Fig.10 It is a schematic diagram of an electrical device using a secondary battery according to one embodiment of the present application as a power source.
[0059] Description of reference numerals:
[0060] 1 Battery Pack
[0061] 2 upper box
[0062] 3 lower box
[0063] 4 Battery Module
[0064] 5 Secondary batteries
[0065] 51 Housing
[0066] 52 Electrode assembly
[0067] 53 Top cover assembly
[0068] 6. Negative electrode
[0069] 61 Current collector
[0070] 60 Active material layer
[0071] 62 First graphite layer
[0072] 63 Lithium titanate layer
[0073] 64 Second graphite layer DETAILED DESCRIPTION
[0074] Below, the embodiments of the negative electrode sheet for secondary batteries and their preparation methods, secondary batteries, battery modules, battery packs and electrical devices of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0075] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0076] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0077] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0078] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0079] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0080] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0081] Lithium-ion batteries in the prior art usually use graphite as the negative electrode active material, but the negative electrode plates using graphite as the negative electrode active material are prone to rebound due to volume changes during the manufacturing process and during the battery charging and discharging process. On the one hand, the rebound of the negative electrode plate causes excessive expansion force of the battery cell, squeezing the diaphragm and causing poor electrolyte infiltration, which in turn increases polarization, causing the battery cell capacity to decay faster and shortening its service life. On the other hand, excessive rebound of the negative electrode plate can also cause the plate corners to break, increasing the safety risk of the battery cell. Therefore, in order to improve the service life and safety performance of lithium-ion batteries, it is urgent to reduce the rebound of the negative electrode plate caused by volume changes during the manufacturing process and during the battery charging and discharging process.
[0082] In the prior art, it has been proposed to use lithium titanate (Li4Ti5O 12 ) is mixed with graphite and applied to the active material layer of the negative electrode to reduce the rebound of the negative electrode by taking advantage of the "zero strain" of lithium titanate. However, the electronic conductivity of lithium titanate is only 10 -13s / cm, which greatly limits the electron transfer between the current collector and the active material layer in the negative electrode sheet, resulting in the degradation of the rate performance of lithium-ion batteries. Moreover, the potential of lithium titanate to lithium is 1.5V, which cannot form a solid electrolyte interface film (SEI film). Therefore, it is difficult for the active material layer mixed with lithium titanate to form a dense SEI film, resulting in repeated destruction and regeneration of the SEI film, aggravating the consumption of active lithium, and thus causing the capacity decay of lithium-ion batteries.
[0083] Therefore, the negative electrode plates of the prior art still need to be improved in reducing the plate rebound rate while ensuring the rate performance of the battery and reducing the capacity attenuation of the battery.
[0084] In one embodiment of the present application, the present application proposes a negative electrode sheet, which includes a current collector and an active material layer disposed on at least one surface of the current collector, the active material layer including:
[0085] First graphite layer;
[0086] a lithium titanate layer; and
[0087] The second graphite layer,
[0088] A first graphite layer is disposed on at least one surface of the current collector, a lithium titanate layer is disposed on a surface of the first graphite layer, a second graphite layer is disposed on a surface of the lithium titanate layer, and
[0089] The OI value of the first graphite layer is greater than or equal to 20.0, and may be 30.0 to 40.0. The OI value of the second graphite layer is less than or equal to 15.0, and may be 8.0 to 12.0.
[0090] Although the mechanism is still unclear, the applicant unexpectedly found that: Figure 1As shown, the present application provides a lithium titanate layer (63) in the active material layer (60), which can reduce the rebound of the negative electrode plate (6) caused by volume change during the manufacturing process and the battery charging and discharging process, thereby improving the service life and safety performance of the lithium ion battery. The lattice constant and volume change of lithium titanate crystals are less than 1% when lithium ions are embedded or extracted. This characteristic of lithium titanate can be called "zero strain". Therefore, providing a lithium titanate layer (63) in the active material layer (60) can reduce the rebound of the negative electrode plate caused by volume change during the charging and discharging process. Moreover, providing a lithium titanate layer (63) can also relieve and / or disperse the stress accumulated in the first and second graphite layers (62, 64) of the negative electrode plate during the manufacturing process, such as cold pressing, thereby reducing the rebound of the plate caused by the slow release of stress during subsequent use. By reducing the rebound of the negative electrode plate, the cycle performance and service life of the battery can be improved, the specific capacity decay caused by the cycle can be reduced, and the battery has very good overcharge and over-discharge resistance characteristics. In addition, by reducing the rebound of the negative electrode plate, it is also possible to avoid the plate from breaking at the corners, thereby improving the safety performance of the battery.
[0091] The lithium titanate layer may include lithium titanate, a conductive agent, a binder, and an optional thickener. In the present application, as long as the lithium titanate can play the role of reducing the rebound of the negative electrode plate as described above, there is no specific restriction on the type of lithium titanate. Optionally, the lithium titanate may be a polycrystalline spherical particle. Optionally, the particle size D50 of the lithium titanate particles may be 4 to 15 μm. The types of conductive agents, binders, and optional thickeners are not specifically limited, and those skilled in the art may select them according to actual needs. The content of lithium titanate, conductive agents, binders, and optional thickeners in the lithium titanate layer is not specifically limited, and those skilled in the art may select them according to actual needs. Optionally, relative to the total weight of the lithium titanate layer, the amount of lithium titanate may be 85 to 96% by weight; the amount of conductive agents may be 0.5 to 10.0% by weight; the amount of binders may be 0.3 to 2.0% by weight; and the amount of optional thickeners may be 0.1 to 1.0% by weight.
[0092] In the present application, by providing a first graphite layer with a higher OI value on at least one surface of the current collector, that is, between the lithium titanate layer and the current collector layer, the problem of rate performance degradation caused by low electronic conductivity of lithium titanate is solved. Specifically, the OI value of the first graphite layer is greater than or equal to 20.0, and can be selected as 30.0-40.0. The first graphite layer has a higher OI value within the above range, which means that a higher proportion of (004) crystal planes parallel to the graphite sheet structure are exposed in the first graphite layer. This structure is very conducive to the flow of electrons on the graphite surface and the transmission of electrons through the current collector, which greatly increases the electronic conductivity of the negative electrode. Moreover, this structure can also enhance the adhesion between the first graphite layer and the current collector. Therefore, providing a first graphite layer with a higher OI value within the above range on the surface of the current collector can fully guarantee the rate performance of the lithium-ion battery by improving the electronic conductivity.
[0093] The first graphite layer may include a first graphite, a conductive agent, a binder, and an optional thickener. The first graphite may be a commercially available product with a certain OI value specification. Optionally, the first graphite may be a graphite having an OI value greater than 2.0 and less than or equal to 6.0, optionally 3.0 to 5.0. The types of conductive agent, binder, and optional thickener are not specifically limited, and those skilled in the art may select them according to actual needs. The content of the first graphite, conductive agent, binder, and optional thickener in the first graphite layer is not specifically limited, and those skilled in the art may select them according to actual needs. Optionally, relative to the total weight of the first graphite layer, the amount of the first graphite may be 90.0 to 98.0% by weight; the amount of the conductive agent may be 0.3 to 4.0% by weight; the amount of the binder may be 0.3 to 2.0% by weight; and the amount of the optional thickener may be 0.1 to 1.0% by weight.
[0094] The OI value of the first graphite layer can be adjusted by changing the OI value of the first graphite, the manufacturing process parameters of the negative electrode plate such as the cold pressing pressure and / or the thickness of the first graphite layer, so that it is greater than or equal to 20.0, and can be optionally adjusted to a range of 30.0 to 40.0.
[0095] In the present application, by providing a second graphite layer with a lower OI value on the surface of the lithium titanate layer, the conduction rate of lithium ions can be increased, the rate performance of the lithium ion battery can be improved, and the densification degree of the SEI film on the surface of the active material layer can be increased, and the consumption of active lithium ions can be delayed, thereby reducing the capacity decay of the battery. Specifically, the OI value of the second graphite layer can be less than or equal to 15.0, and can be selected as 8.0 to 12.0. The second graphite layer has a lower OI value within the above range, which means that a higher proportion of (110) crystal planes perpendicular to the graphite sheet structure are exposed in the second graphite layer. This structure is very conducive to the embedding and extraction of lithium ions in graphite, thereby increasing the conduction rate of lithium ions. Moreover, when the (110) crystal plane of graphite contacts the electrolyte, an SEI film can be formed thereon, while an SEI film is not easily formed on the (004) crystal plane. Therefore, the (110) crystal plane with a higher exposure ratio can also increase the density of the SEI film formed on the surface of the negative electrode active material layer, thereby delaying the consumption of active lithium ions during the battery charge and discharge process and reducing the capacity decay of the battery. Therefore, providing a second graphite layer with a lower OI value within the above range on the surface of the lithium titanate layer can fully guarantee the rate performance of the lithium ion battery while reducing the capacity decay of the lithium ion battery.
[0096] The second graphite layer may include a second graphite, a conductive agent, a binder, and an optional thickener. The second graphite may be a commercially available product with a certain OI value specification. Optionally, the second graphite may be a graphite having an OI value greater than or equal to 0.5 and less than 2.0, optionally 1.0 to 1.5. The types of conductive agent, binder, and optional thickener are not specifically limited, and those skilled in the art may select them according to actual needs. The content of the second graphite, conductive agent, binder, and optional thickener in the second graphite layer is not specifically limited, and those skilled in the art may select them according to actual needs. Optionally, relative to the total weight of the second graphite layer, the amount of the second graphite may be 90.0 to 98.0% by weight; the amount of the conductive agent may be 0.3 to 4.0% by weight; the amount of the binder may be 0.3 to 2.0% by weight; and the amount of the optional thickener may be 0.1 to 1.0% by weight.
[0097] The OI value of the second graphite layer can be adjusted by changing the OI value of the second graphite, the manufacturing process parameters of the negative electrode sheet such as the cold pressing pressure and / or the thickness of the second graphite layer, so that it is less than or equal to 15.0, and can be optionally within the range of 8.0 to 12.0.
[0098] In some embodiments, the thickness of the first graphite layer may be less than or equal to 100 μm. When the thickness of the first graphite layer is less than or equal to 100 μm, an OI value of the first graphite layer greater than or equal to 20.0, optionally 30.0 to 40.0, may be achieved; at the same time, the adverse effect of the volume change of graphite on the rebound characteristics of the negative electrode sheet during the manufacture and use of the lithium-ion battery is minimized, and the productivity of the negative electrode sheet can be improved.
[0099] In some embodiments, the thickness of the lithium titanate layer may be 25 to 50 μm. When the thickness of the lithium titanate layer is greater than or equal to 25 μm, the lithium titanate layer can fully play the role of reducing the rebound of the negative electrode plate. When the thickness of the lithium titanate layer is less than or equal to 50 μm, the adverse effect of the low electronic conductivity of lithium titanate on the electronic transmission characteristics of the negative electrode plate is minimized, thereby further ensuring the rate performance of the lithium-ion battery.
[0100] In some embodiments, the thickness of the second graphite layer is less than or equal to 100 μm. When the thickness of the second graphite layer is less than or equal to 100 μm, an OI value of the second graphite layer less than or equal to 15.0, optionally 8.0 to 12.0, can be achieved; at the same time, the adverse effect of the volume change of graphite on the rebound characteristics of the negative electrode sheet during the manufacture and use of the lithium-ion battery can be minimized, and the productivity of the negative electrode sheet can be improved.
[0101] In some embodiments, the thickness of the active material layer is 50 to 150 μm. When the thickness of the active material layer is greater than or equal to 50 μm, the energy density of the negative electrode plate can be ensured, thereby ensuring the capacity of the battery. When the thickness of the active material layer is less than or equal to 150 μm, the wettability of the electrode plate during the preparation process can be ensured, and the production efficiency can be improved.
[0102] In some embodiments, the compaction density of the negative electrode sheet is 0.9 to 1.8 g / cm 3 The compaction density of the negative electrode sheet is mainly affected by the cold pressing pressure, and is also affected by the characteristics of the active material in the active material layer, such as the grain size of lithium titanate. When the compaction density of the negative electrode sheet is greater than or equal to 0.9g / cm 3 When the compaction density of the negative electrode sheet is less than or equal to 1.8g / cm 3 At the same time, it can ensure the wettability of the electrode during the preparation process and improve the production efficiency of the electrode. It can also further reduce the rebound of the negative electrode sheet, thereby further slowing down the capacity attenuation caused by excessive battery expansion force, and further reduce the safety risks brought by the rebound of the negative electrode sheet, and further improve the battery's rate performance and cycle performance.
[0103] The present application also provides a method for preparing a negative electrode sheet, comprising:
[0104] providing a current collector;
[0105] forming a first graphite layer including a first graphite on at least one surface of the current collector;
[0106] forming a lithium titanate layer including lithium titanate on a surface of the first graphite layer;
[0107] forming a second graphite layer including a second graphite on the surface of the lithium titanate layer to obtain a laminate having an active material layer on at least one surface of the current collector, wherein the active material layer includes the first graphite layer, the lithium titanate layer and the second graphite layer;
[0108] Cold pressing the laminate to obtain a negative electrode sheet;
[0109] The OI value of the first graphite is greater than 2.0 and less than or equal to 6.0, and may be 3.0 to 5.0, and the OI value of the second graphite is greater than or equal to 0.5 and less than 2.0, and may be 1.0 to 1.5. Both the first graphite and the second graphite may be commercially available products with corresponding OI values.
[0110] The preparation method of the present application can effectively prepare the negative electrode sheet of the first aspect of the present application.
[0111] In some embodiments, the stack can be formed by coating the first graphite layer, the lithium titanate layer, and the second graphite layer layer by layer in a conventional coating manner. The coating can be formed by mixing the first graphite, lithium titanate, or the second graphite, which serves as the negative electrode active material, and the conductive agent, the binder, the optional thickener, and the deionized water serving as the solvent. Optionally, the mass ratio of the active material to the solvent deionized water in the slurry can be 1:0.5-2, optionally 1:0.8-1.5. Optionally, the shipping viscosity of the slurry can be 5000-25000mPa·s. If the amount of deionized water added is too low, the slurry will be too concentrated, the viscosity of the slurry will be too large, it will be difficult to coat, and the uniformity of the coating layer will be poor; if the amount of deionized water added is too high, the slurry will be too thin. In order to achieve a fixed coating thickness, it is necessary to increase the coating process time, reducing the efficiency of pole piece production.
[0112] Optionally, in the process of preparing the negative electrode sheet, before the cold pressing process, the thickness of the first graphite layer formed on at least one surface of the stack can be less than or equal to 200 μm; the thickness of the lithium titanate layer formed on the surface of the first graphite layer can be less than or equal to 100 μm; the thickness of the second graphite layer formed on the surface of the lithium titanate layer can be less than or equal to 200 μm; the thickness of the active material layer including the first graphite layer, the lithium titanate layer and the second graphite layer can be 100 to 300 μm.
[0113] In some embodiments, the cold pressing pressure may be 15 to 70T. Optionally, the cold pressing pressure may be determined according to demand, so as to be combined with factors such as the OI value and layer thickness of the graphite raw material so that the OI values of the first graphite layer and the second graphite layer fall within the specific ranges described above. Moreover, the selection of the cold pressing pressure within the above range may also advantageously control the active material of the negative electrode sheet to achieve a reasonable compaction density. When the pressure is greater than or equal to 15T, the compaction density of the negative electrode sheet may be ensured, thereby ensuring the energy density of the battery. When the cold pressing pressure is less than or equal to 70T, the excessive density of the electrode sheet may be avoided, resulting in reduced wettability of the electrolyte, thereby ensuring the production efficiency of the battery. At the same time, the particles in the active material layer may be prevented from breaking during the pressing process, thereby affecting the safety of the battery.
[0114] In some embodiments, after the stack is cold pressed, the OI value of the first graphite layer formed may be greater than or equal to 20.0, and may be 30.0 to 40.0, and the OI value of the second graphite layer formed may be less than or equal to 15.0, and may be 8.0 to 12.0. As described above, after the stack is cold pressed, when the OI values of the first graphite layer and the second graphite layer of the obtained negative electrode sheet are respectively adjusted to the above ranges, the rate performance of the lithium ion battery using the negative electrode sheet can be fully guaranteed, while reducing the capacity attenuation of the lithium ion battery.
[0115] In some embodiments, after cold pressing the laminate, the compaction density of the negative electrode sheet formed can be 0.9 to 1.8 g / cm 3 As described above, after the laminate is cold pressed, when the compaction density of the obtained negative electrode sheet is adjusted to the above range, the capacity of the lithium-ion battery using the negative electrode sheet can be fully guaranteed, while ensuring the wettability of the sheet during the preparation process and the production efficiency of the sheet.
[0116] Optionally, after the stack is cold pressed, the thickness of the first graphite layer may be less than or equal to 100 μm; the thickness of the lithium titanate layer may be 25 to 50 μm; and the thickness of the second graphite layer may be less than or equal to 100 μm.
[0117] Optionally, after the stack is cold-pressed, the thickness of the formed active material layer may be 50 to 150 μm.
[0118] The present application also provides a secondary battery, comprising:
[0119] Positive electrode;
[0120] The negative electrode sheet of the present application as described above, or the negative electrode sheet prepared according to the preparation method of the present application as described above;
[0121] Electrolytes; and
[0122] Diaphragm.
[0123] The present application also provides a battery module, which includes the secondary battery of the present application as described above.
[0124] The present application also provides a battery pack, which includes the battery module of the present application as described above.
[0125] The present application also provides an electrical device, which includes the secondary battery of the present application as described above, the battery module of the present application as described above, or the battery pack of the present application as described above.
[0126] In the negative electrode plate of the present application, by providing an active material layer including a first graphite layer with a specific higher OI value, a lithium titanate layer and a second graphite layer with a specific lower OI value on the current collector, the rebound of the negative electrode plate caused by volume change during the manufacturing process and the battery charging and discharging process can be effectively reduced, thereby improving the service life and safety performance of the lithium-ion battery, while fully ensuring the battery's rate performance and reducing the battery's capacity attenuation.
[0127] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.
[0128] In one embodiment of the present application, a secondary battery is provided.
[0129] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0130] [Positive electrode]
[0131] The positive electrode sheet may include a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. As an example, the positive current collector has two surfaces opposite to each other in its thickness direction, and the positive active material layer is disposed on any one or both of the two opposite surfaces of the positive current collector.
[0132] The positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0133] The positive electrode active material layer includes a positive electrode active material. The positive electrode active material includes, but is not limited to, lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium titanate, etc. The positive electrode active material may use one or more of these.
[0134] The positive electrode active material layer may also optionally include a binder. However, there is no specific restriction on the type of binder, and those skilled in the art may select according to actual needs. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0135] The positive electrode active material layer may also optionally include a conductive agent. However, there is no specific limitation on the type of the conductive agent, and those skilled in the art may select it according to actual needs. As an example, the conductive agent used for the positive electrode active material layer may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0136] The preparation of the positive electrode sheet can be carried out according to methods known in the art. As an example, the positive electrode active material, the conductive agent and the binder can be dispersed in a solvent (such as N-methylpyrrolidone (NMP)) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained.
[0137] [Negative electrode]
[0138] The negative electrode sheet in the secondary battery of the present application uses the negative electrode sheet for the secondary battery as described above, which includes a current collector and an active material layer arranged on at least one surface of the current collector, and the active material layer includes a first graphite layer, a lithium titanate layer and a second graphite layer. The first graphite layer is arranged on at least one surface of the current collector, the lithium titanate layer is arranged on the surface of the first graphite layer, and the second graphite layer is arranged on the surface of the lithium titanate layer, and the OI value of the first graphite layer is greater than or equal to 20.0, and can be selected from 30.0 to 40.0, and the OI value of the second graphite layer is less than or equal to 15.0, and can be selected from 8.0 to 12.0.
[0139] In the case where the active material layer is formed on only one surface of the current collector, the current collector and the active material layer of the negative electrode sheet may have the following characteristics: Figure 1 In the case where the active material layers are formed on both surfaces of the current collector, the two active material layers of the negative electrode sheet may have a symmetrical structure.
[0140] The negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). The first graphite layer, the lithium titanate layer and the second graphite layer in the negative electrode active material layer may include a binder, a conductive agent and other additives such as an optional thickener.
[0141] The conductive agents used in the first graphite layer, the lithium titanate layer and the second graphite layer can be the same or different, and those skilled in the art can select them according to their needs. As an example, the conductive agent can be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0142] The binders used in the first graphite layer, the lithium titanate layer, and the second graphite layer can be the same or different, and those skilled in the art can select them according to their needs. As an example, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0143] The other additives used in the first graphite layer, the lithium titanate layer and the second graphite layer can be the same or different, and those skilled in the art can select them according to their needs. As an example, the additives can optionally include a thickener, such as sodium carboxymethyl cellulose (CMC-Na) and the like.
[0144] By the preparation method of the present application, a first graphite layer including a first graphite can be formed on at least one surface of the current collector, a lithium titanate layer including lithium titanate can be formed on the surface of the first graphite layer, and a second graphite layer including a second graphite can be formed on the surface of the lithium titanate layer, thereby obtaining an active material layer including the first graphite layer, the lithium titanate layer and the second graphite layer, and then the obtained laminate having the active material layer on at least one surface of the current collector is cold pressed, and after drying, cold pressing and other processes, a negative electrode sheet is obtained. The OI value of the first graphite is greater than 2.0 and less than or equal to 6.0, and can be selected from 3.0 to 5.0. The OI value of the second graphite is greater than or equal to 0.5 and less than 2.0, and can be selected from 1.0 to 1.5.
[0145] As an example, the first graphite, conductive agent, binder and optional other additives can be dispersed in a solvent (such as deionized water) to form a uniform slurry, which is coated on at least one surface of the negative electrode current collector by a conventional coating process, and then dried to obtain a first graphite layer. Lithium titanate, conductive agent, binder and optional other additives are dispersed in a solvent (such as deionized water) to form a uniform slurry, which is coated on the surface of the first graphite layer by a conventional coating process, and then dried to obtain a lithium titanate layer. The second graphite, conductive agent, binder and optional other additives are dispersed in a solvent (such as deionized water) to form a uniform slurry, which is coated on the surface of the lithium titanate layer by a conventional coating process, and then dried to obtain a second graphite layer. Next, the obtained laminate including the current collector, the first graphite layer, the lithium titanate layer and the second graphite layer is cold pressed at a pressure of 15 to 70T to obtain a negative electrode sheet.
[0146] [Electrolytes]
[0147] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0148] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0149] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0150] As an example, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0151] In some embodiments, the electrolyte may also optionally include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, additives for improving battery overcharge performance, additives for improving battery high temperature performance, additives for improving battery low temperature performance, etc.
[0152] [Diaphragm]
[0153] The separator separates the positive electrode from the negative electrode to prevent short circuits inside the battery, while allowing active ions to pass through the separator and move between the positive and negative electrodes. In the secondary battery of the present application, there is no particular restriction on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0154] In some embodiments, the material of the diaphragm can be selected from one or more of a glass fiber film, a non-woven film, a polyethylene (PE) film, a polypropylene (PP) film, a polyvinylidene fluoride film, and a multilayer composite film containing one or more of them. The diaphragm can be a single-layer diaphragm or a multilayer composite diaphragm, without particular limitation. When the diaphragm is a multilayer composite diaphragm, the materials of each layer can be the same or different, without particular limitation.
[0155] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process. In the present application, when assembling the electrode assembly, the second graphite layer on the negative electrode sheet faces the separator.
[0156] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte as described above.
[0157] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0158] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0159] In some embodiments, reference Figure 6 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0160] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0161] Figure 7 4 is an example of a battery module. Figure 7 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0162] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0163] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0164] Figure 8 and Fig. 9 1 is a battery pack 1 as an example. Figure 8 and Fig. 9 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0165] In addition, the present application also provides an electrical device, which includes a secondary battery, a battery module, or a battery pack provided in the present application. The secondary battery, the battery module, or the battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0166] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0167] Fig.10 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0168] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0169] Example
[0170] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be obtained commercially.
[0171] Preparation of negative electrode
[0172] The first graphite with an OI value greater than 2.0 and less than or equal to 6.0, the conductive agent carbon black (Beitrui New Materials Group Co., Ltd., model BSC), the binder styrene butadiene rubber (SBR) (China Petroleum Jilin Petrochemical Company, model 1520), and the thickener sodium hydroxymethyl cellulose (CMC) (Japan Daicel Corporation, model 200) are added to deionized water in a mass ratio of 97.2:0.8:0.8:1.2 and fully stirred, and after mixing evenly, a slurry (solid content of 50%) for forming a first graphite layer is prepared. Through conventional processes, the above slurry is evenly coated on a current collector copper foil with a thickness of 6 μm, and then dried at a temperature of 80 to 150° C., thereby forming a first graphite layer on the current collector aluminum foil.
[0173] Next, lithium titanate (Jiawei New Energy Co., Ltd., model T200), conductive agent carbon black, binder styrene butadiene rubber (SBR), thickener sodium hydroxymethyl cellulose (CMC) were added to deionized water in a mass ratio of 97.2:0.8:0.8:1.2 and fully stirred, and mixed evenly to prepare a slurry (solid content 50%) for forming a lithium titanate layer. Through conventional processes, the above slurry was evenly coated on the first graphite layer formed above, and then dried at a temperature of 80 to 150°C to form a lithium titanate layer on the first graphite layer.
[0174] Next, the second graphite with an OI value greater than or equal to 0.5 and less than 2.0, the conductive agent carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are added to deionized water in a weight ratio of 97.2:0.8:0.8:1.2 and fully stirred, and after being mixed evenly, a slurry (solid content 50%) for forming a second graphite sheet layer is prepared. The slurry is evenly coated on the lithium titanate layer formed above through conventional processes, and then dried at a temperature of 80 to 150° C., thereby forming a second graphite layer on the lithium titanate layer.
[0175] The electrode sheet formed as above, in which the active material layer including the first graphite layer, the lithium titanate layer and the second graphite layer are coated on the current collector, is cold pressed at a pressure of 15 to 70 T, and then cut to obtain a negative electrode sheet.
[0176] Preparation of batteries
[0177] In the embodiments of the present application, the battery cell is prepared by the following method.
[0178] (1) Preparation of positive electrode sheet
[0179] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM 811) (Ningbo Rongbai New Energy Technology Co., Ltd., model S85E), conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) (Kureha Co., Ltd., Japan, model W9200) were mixed in a mass ratio of 97:1.5:1.5 and solvent N-methylpyrrolidone (NMP) was added, and then fully stirred and mixed to prepare positive electrode slurry (solid content 70%). The positive electrode slurry was prepared by conventional process at 0.2 mg / mm 2 The coating amount is evenly coated on the current collector aluminum foil with a thickness of 13 μm, and then dried at a temperature of 100-130° C., cold pressed at a pressure of 40 T, and then cut to obtain the positive electrode sheet.
[0180] (2) Preparation of electrolyte
[0181] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, 12.5% LiPF6 lithium salt was added and dissolved in the organic solvent (molar concentration 1.2 mol / L), and stirred evenly to obtain an electrolyte for lithium-ion batteries.
[0182] (3) Preparation of batteries
[0183] The positive electrode sheet obtained in the above steps, the polypropylene film (Yunnan Enjie New Materials Co., Ltd., model ND7) as a diaphragm and the negative electrode sheet are stacked in the above order so that the second graphite layer on the negative electrode sheet faces the diaphragm. Then wind to obtain a bare cell. The pole lugs are welded on the bare cell, and the bare cell is loaded into an aluminum shell. The assembled cell is baked at 100°C to remove water, and then the electrolyte is injected to obtain an uncharged battery. The uncharged battery is subjected to static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain a lithium-ion battery.
[0184] Performance Testing
[0185] (1) OI values of the first and second graphite layers
[0186] The OI values of the first and second graphite layers were determined by X-ray diffraction on a polycrystalline X-ray diffractometer (Bruker, D8 Discover). The sample to be tested was placed horizontally on the sample stage and scanned in continuous mode (scanning interval 10-80°, scanning speed 2° / min) to obtain the corresponding diffraction spectrum. According to the diffraction spectrum, the diffraction peak intensity of the (004) crystal plane was determined to be I(004), and the diffraction peak intensity of the (110) crystal plane was determined to be I(110). The OI value calculation formula is as follows:
[0187] OI=I(004) / I(110)
[0188] In the above measurement, the samples to be tested of the first graphite layer and the second graphite layer are obtained by the following method:
[0189] Take a 10cm×10cm negative electrode sheet, the thickness of the first graphite layer, lithium titanate layer and second graphite layer of the negative electrode sheet are d1, d2 and d3 respectively, and use a scraper to evenly scrape off the graphite of d3 / 2 thickness on the surface, and the scraped thickness is determined by a micrometer. Cut a 2cm×2cm small piece from the negative electrode sheet with the specified thickness scraped off obtained as described above to obtain a sample for measuring the OI value of the second graphite layer.
[0190] Take a 10cm×10cm negative electrode sheet, the thickness of the first graphite layer, lithium titanate layer and second graphite layer of the negative electrode sheet are d1, d2 and d3 respectively, use a scraper to evenly scrape off the graphite of the thickness of (d3+d2+d1 / 2) on the surface, and the scraped thickness is determined by a micrometer. Cut a 2cm×2cm small piece from the negative electrode sheet with the specified thickness scraped off obtained as described above to obtain a sample for measuring the OI value of the first graphite layer.
[0191] (2) Negative electrode rebound rate
[0192] Use a micrometer to measure the thickness of the negative electrode sheet. The thickness of the negative electrode sheet after cold pressing is recorded as R. In the preparation of the battery, the positive electrode sheet, the separator and the negative electrode sheet are stacked, and then after sufficient rebound, before being wound into a bare battery cell, the thickness of the negative electrode sheet is measured and recorded as S. After full charge, the thickness of the negative electrode sheet is measured and recorded as T. After the prepared lithium-ion battery is cycled for 100 cycles at a temperature of 45°C under the cycle conditions of a preload of 200kgf, a charging rate of 0.5C and a discharge rate of 1C, the thickness of the negative electrode sheet is measured and recorded as U. After 200 cycles under the above-mentioned cycle conditions, the thickness of the negative electrode sheet is measured and recorded as V. The rebound rate of the negative electrode sheet at different stages is calculated according to the following formula:
[0193] Rebound rate (winding) = (S / R-1) × 100%
[0194] Rebound rate (full charge) = (T / R-1) × 100%
[0195] Rebound rate (100 cycles) = (U / R-1) × 100%
[0196] Rebound rate (200 cycles) = (V / R-1) × 100%
[0197] By plotting the rebound rate at different stages as the vertical axis, we can obtain a rebound rate change trend graph of the negative electrode.
[0198] (3) Battery expansion force
[0199] Before charging and discharging the battery, a fixture consisting of three aluminum plates is used to clamp the battery and the pressure sensor. Specifically, the pressure sensor is placed in the upper space between the first and second aluminum plates, and the battery is placed in the lower space between the second and third aluminum plates. Then, a preload force F0 of 200 kgf is applied to fix the fixture with bolts.
[0200] Next, the battery was cycled at 45°C under the conditions of a charge rate of 0.5C and a discharge rate of 1C. The reading of the pressure sensor in the fixture when the battery cell is fully charged during each cycle is recorded as the battery expansion force F of the lithium ion corresponding to the number of cycles. n With the number of cycles as the horizontal axis and the expansion force of the lithium-ion battery corresponding to the number of cycles as the vertical axis, a curve graph showing the expansion force changing with the number of cycles can be obtained.
[0201] The battery expansion force growth rate E per cycle n Calculated according to the following formula:
[0202] E n =[(F n –200) / 200)]×100%
[0203] (4) Cycle capacity retention rate
[0204] At 45°C, the battery was charged to 4V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4V, left for 5 minutes, and then discharged to 2.5V at a constant current of 1 / 3C. The resulting capacity was recorded as the initial capacity C0. Then, the battery was cycled under the same conditions as above, and the discharge capacity C of the battery after the nth cycle was recorded. n The battery capacity retention rate P after each cycle n Calculated according to the following formula:
[0205] P n =(C n / C0)×100%
[0206] With the number of cycles as the horizontal axis and the cycle capacity retention rate of the lithium-ion battery after the corresponding number of cycles as the vertical axis, a curve graph showing the cycle capacity retention rate of the battery changing with the number of cycles can be obtained.
[0207] (5) Rate capacity retention
[0208] At 25°C, the battery was charged to 4V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4V, left for 5 minutes, and then discharged to 2.5V at 0.1C. The average capacity obtained after 5 cycles was recorded as the initial capacity D0. Then, the battery was charged under the same conditions as above, discharged at 1C, and the average capacity obtained after 5 cycles was recorded as the initial capacity D1. The rate capacity retention rate Q1 of the battery is calculated according to the following formula:
[0209] Q1=(D1 / D0)×100%
[0210] Similarly, the rate capacity retention rate Q2 of the battery is measured. Specifically, at 25°C, the battery is charged to 4V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4V, left for 5 minutes, and then discharged to 2.5V at 0.1C. The average capacity obtained after 5 cycles is recorded as the initial capacity D0. Then, the battery is charged under the same conditions as above, discharged at 2C, and the average capacity obtained after 5 cycles is recorded as the initial capacity D2. The rate capacity retention rate Q2 of the battery is calculated according to the following formula:
[0211] Q2=(D2 / D0)×100%
[0212] Example 1
[0213] According to the method for manufacturing the negative electrode sheet described above, a slurry for forming the first graphite layer is prepared using a first graphite with an OI value of 5.0 (Bai Te Rui New Materials Group Co., Ltd., model BFC-18). The slurry is heated to 0.04 mg / mm 2 The coating amount was coated on both surfaces of the current collector, and then dried at 100°C to form a first graphite layer with a thickness of 60 μm; the slurry for forming the lithium titanate layer was coated at 0.12 mg / mm 2 The coating amount of the first graphite layer was coated on the first graphite layer, and then dried at 100° C. to form a lithium titanate layer with a thickness of 80 μm; a second graphite with an OI value of 1.0 (Beitrui New Materials Group Co., Ltd., model GSN) was used to prepare a slurry for forming the second graphite layer, and the slurry was heated to 0.04 mg / mm 2The coating amount is coated on the lithium titanate layer, and then dried at 100°C to form a second graphite layer with a thickness of 60μm. As a result, active material layers including a first graphite layer, a lithium titanate layer and a second graphite layer are coated on both surfaces of the current collector. Next, the pole sheet coated with the above-mentioned active material layer on the current collector is cold pressed at a pressure of 40T, and then cut to obtain the negative electrode sheet of Example 1. In Example 1, after cold pressing, the thicknesses of the first graphite layer, the lithium titanate layer and the second graphite layer in the obtained negative electrode sheet are 30μm, 40μm and 30μm, respectively. The thickness R of the negative electrode sheet obtained by cold pressing is 206μm, and the compaction density is 1.6g / cm 3 .
[0214] By the test method described above, the OI values of the first graphite layer and the second graphite layer in the negative electrode sheet of Example 1 were measured respectively, and the results are shown in Table 1.
[0215] A lithium-ion battery was prepared using the negative electrode sheet of Example 1 by the method described above. During the preparation process, the rebound rate of the negative electrode sheet of Example 1 before winding was measured by the method described above. In addition, the rebound rate of the negative electrode sheet after full charge, the rebound rate of the negative electrode sheet after 100 cycles, and the rebound rate of the negative electrode sheet after 200 cycles of the lithium-ion battery prepared using the negative electrode sheet of Example 1 were measured by the method described above. The measurement results of the rebound rate of the negative electrode sheet of Example 1 at different stages are shown in Table 1. The rebound rate change trend diagram of the negative electrode sheet of Example 1 is shown in Table 1. Figure 2 shown.
[0216] The cyclic expansion force of the lithium ion battery prepared in Example 1 was measured by the test method described above. The results of the cyclic expansion force and the corresponding expansion force growth rate of the lithium ion battery prepared in Example 1 after 200 cycles are also shown in Table 1. The curve of the expansion force of the lithium ion battery prepared in Example 1 as a function of the number of cycles is shown in Table 1. Figure 3a shown.
[0217] The cycle capacity retention rate of the lithium ion battery prepared in Example 1 was measured by the test method described above. The cycle capacity retention rate P of the lithium ion battery prepared in Example 1 after 200 cycles 200 The results are also shown in Table 1. The curve diagram of the cycle capacity retention rate of the lithium ion battery prepared in Example 1 as a function of the number of cycles is shown in Table 1. Figure 3b shown.
[0218] The rate capacity retention rates Q1 and Q2 of the lithium ion battery prepared in Example 1 were measured by the test method described above. The measurement results are also shown in Table 1.
[0219] Comparative Example 1
[0220] A negative electrode sheet including only an active material layer of a second graphite layer is formed on a current collector copper foil having a thickness of 6 μm. In Control Example 1, the method for forming the second graphite layer is substantially the same as the corresponding method in Example 1, but the thickness of the active material layer including the second graphite layer after the coating and drying process is 200 μm. Next, the sheet coated with the above-mentioned active material layer on the current collector is cold pressed at a pressure of 40 T, and then cut to obtain the negative electrode sheet of Control Example 1. In Control Example 1, after cold pressing, the thickness of the active material layer is 100 μm. The thickness R of the negative electrode sheet obtained by cold pressing is 206 μm, and the compaction density is 1.6 g / cm 3 .
[0221] The OI value of the second graphite layer in the negative electrode sheet of Control Example 1 was measured by the test method described above, and the results are also shown in Table 1.
[0222] The negative electrode sheet of Control Example 1 was used to prepare a lithium-ion battery by the method described above. The rebound rate of the negative electrode sheet of Control Example 1 at different stages was measured by the method described above, and the results are also shown in Table 1. The rebound rate change trend of the negative electrode sheet of Control Example 1 is shown in Table 1. Figure 2 shown.
[0223] The cyclic expansion force of the lithium ion battery prepared in Control Example 1 was measured by the test method described above. The results of the cyclic expansion force and the corresponding expansion force growth rate of the lithium ion battery prepared in Control Example 1 after 200 cycles are also shown in Table 1. The curve of the expansion force of the lithium ion battery prepared in Control Example 1 as a function of the number of cycles is shown in Table 1. Figure 3a shown.
[0224] The cycle capacity retention rate of the lithium ion battery prepared in Control Example 1 was measured by the test method described above. The cycle capacity retention rate P of the lithium ion battery prepared in Control Example 1 after 200 cycles 200 The results are also shown in Table 1. The curve diagram of the cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 1 as a function of the number of cycles is shown in Table 1. Figure 3b shown.
[0225] The rate capacity retention rates Q1 and Q2 of the lithium ion battery prepared in Control Example 1 were measured by the test method described above. The measurement results are also shown in Table 1.
[0226] Comparative Example 2
[0227] A negative electrode sheet including only an active material layer of a first graphite layer is formed on a current collector copper foil having a thickness of 6 μm. In Control Example 2, the method for forming the first graphite layer is basically the same as the corresponding method in Example 1, except that the thickness of the active material layer including only the first graphite layer after the coating and drying steps is 200 μm. Next, the sheet coated with the above-mentioned active material layer on the current collector is cold pressed at a pressure of 40 T, and then cut to obtain the negative electrode sheet of Control Example 2. In Control Example 2, after cold pressing, the thickness of the active material layer is 100 μm. The thickness R of the negative electrode sheet obtained by cold pressing is 206 μm, and the compaction density is 1.6 g / cm 3 .
[0228] The OI value of the first graphite layer in the negative electrode sheet of Control Example 2 was measured by the test method described above, and the results are also shown in Table 1.
[0229] The negative electrode sheet of Control Example 2 was used to prepare a lithium-ion battery by the method described above. The rebound rate of the negative electrode sheet of Control Example 2 at different stages was measured by the method described above, and the results are also shown in Table 1. The rebound rate change trend of the negative electrode sheet of Control Example 2 is shown in Table 1. Figure 2 shown.
[0230] The cyclic expansion force of the lithium ion battery prepared in Control Example 2 was measured by the test method described above. The results of the cyclic expansion force and the corresponding expansion force growth rate of the lithium ion battery prepared in Control Example 2 after 200 cycles are also shown in Table 1. The curve of the expansion force of the lithium ion battery prepared in Control Example 2 as a function of the number of cycles is shown in Table 1. Figure 3a shown.
[0231] The cycle capacity retention rate of the lithium ion battery prepared in Control Example 2 was measured by the test method described above. The cycle capacity retention rate P of the lithium ion battery prepared in Control Example 2 after 200 cycles 200 The results are also shown in Table 1. The curve diagram of the cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 2 as a function of the number of cycles is shown in Table 1. Figure 3b shown.
[0232] The rate capacity retention rates Q1 and Q2 of the lithium ion battery prepared in Control Example 2 were measured by the test method described above. The measurement results are also shown in Table 1.
[0233] Comparative Example 1
[0234] A negative electrode sheet including only an active material layer including a lithium titanate layer and a second graphite layer is formed on a current collector copper foil having a thickness of 6 μm. In Comparative Example 1, the method for forming the lithium titanate layer and the second graphite layer is substantially the same as the corresponding method in Example 1. The thicknesses of the lithium titanate layer and the second graphite layer formed after the coating and drying processes in Comparative Example 1 are 100 μm and 100 μm, respectively. Next, the sheet coated with the above-mentioned active material layer on the current collector is cold pressed at a pressure of 40 T, and then cut to obtain the negative electrode sheet of Comparative Example 1. In Comparative Example 1, after cold pressing, the thickness of the active material layer is 100 μm. The thickness R of the negative electrode sheet obtained by cold pressing is 206 μm, and the compaction density is 1.6 g / cm 3 The OI value of the second graphite layer in the negative electrode sheet of Comparative Example 1 was measured by the test method described above, and the results are also shown in Table 1.
[0235] The negative electrode sheet of Comparative Example 1 was used to prepare a lithium ion battery by the method described above. The rebound rate of the negative electrode sheet of Comparative Example 1 at different stages was measured by the method described above, and the results are also shown in Table 1. The rebound rate change trend of the negative electrode sheet of Comparative Example 1 is shown in Table 1. Figure 2 shown.
[0236] The cyclic expansion force of the lithium ion battery prepared in Comparative Example 1 was measured by the test method described above. The results of the cyclic expansion force and the corresponding expansion force growth rate of the lithium ion battery prepared in Comparative Example 1 after 200 cycles are also shown in Table 1. The curve of the expansion force of the lithium ion battery prepared in Comparative Example 1 as a function of the number of cycles is shown in Table 1. Figure 3a shown.
[0237] The cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 1 was measured by the test method described above. The cycle capacity retention rate P of the lithium ion battery prepared in Comparative Example 1 after 200 cycles 200 The results are also shown in Table 1. The curve diagram of the cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 1 as a function of the number of cycles is shown in Table 1. Figure 3b shown.
[0238] The rate capacity retention rates Q1 and Q2 of the lithium ion battery prepared in Comparative Example 1 were measured by the test method described above. The measurement results are also shown in Table 1.
[0239] Comparative Example 2
[0240] A negative electrode sheet including only an active material layer of a first graphite layer and a lithium titanate layer is formed on a current collector copper foil having a thickness of 6 μm. In Comparative Example 2, the method for forming the first graphite layer and the lithium titanate layer is substantially the same as the corresponding method in Example 1. The thicknesses of the first graphite layer and the lithium titanate layer formed after the coating and drying steps in Comparative Example 2 are 100 μm and 100 μm, respectively. Next, the sheet coated with the above-mentioned active material layer on the current collector is cold pressed at a pressure of 40 T, and then cut to obtain the negative electrode sheet of Comparative Example 2. In Comparative Example 2, after cold pressing, the thickness of the active material layer is 100 μm. The thickness R of the obtained negative electrode sheet is 206 μm, and the compaction density is 1.6 g / cm 3 .
[0241] The OI value of the first graphite layer in the negative electrode sheet of Comparative Example 2 was measured by the test method described above, and the results are also shown in Table 1.
[0242] The negative electrode sheet of Comparative Example 2 was used to prepare a lithium ion battery by the method described above. The rebound rate of the negative electrode sheet of Comparative Example 2 at different stages was measured by the method described above, and the results are also shown in Table 1. The rebound rate change trend of the negative electrode sheet of Comparative Example 2 is shown in Table 1. Figure 2 shown.
[0243] The cyclic expansion force of the lithium ion battery prepared in Comparative Example 2 was measured by the test method described above. The results of the cyclic expansion force and the corresponding expansion force growth rate of the lithium ion battery prepared in Comparative Example 2 after 200 cycles are also shown in Table 1. The curve of the expansion force of the lithium ion battery prepared in Comparative Example 2 as a function of the number of cycles is shown in Table 1. Figure 3a shown.
[0244] The cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 2 was measured by the test method described above. The cycle capacity retention rate P of the lithium ion battery prepared in Comparative Example 2 after 200 cycles 200 The results are also shown in Table 1. The curve diagram of the cycle capacity retention rate of the lithium ion battery prepared in Comparative Example 2 as a function of the number of cycles is shown in Table 1. Figure 3b shown.
[0245] The rate capacity retention rates Q1 and Q2 of the lithium ion battery prepared in Comparative Example 2 were measured by the test method described above. The measurement results are also shown in Table 1.
[0246] Table 1
[0247]
[0248] It can be seen from the results in Table 1 that in Example 1, the active material layer of the negative electrode plate includes a first graphite layer with a relatively high OI value, a lithium titanate layer, and a second graphite layer with a relatively low OI value. Under the joint action of the above layers in the active material layer, the rebound of the negative electrode plate during the manufacturing process and the battery charge and discharge cycle is suppressed, while the rate performance of the lithium ion battery is fully guaranteed, and the capacity attenuation of the lithium ion battery during the cycle is significantly reduced.
[0249] In both Comparative Examples 1 and 2, the negative electrode sheet does not include lithium titanate, so the rebound of the negative electrode sheet during the manufacturing process and the cycle of the lithium-ion battery cannot be suppressed. Figure 2 As shown in Figure 1, during the manufacturing process of lithium-ion batteries, the rebound rate of the negative electrode sheet is obviously too high; Figure 3a As shown in Figure 2, during the charge and discharge cycle of lithium-ion batteries, the expansion force of the battery is also significantly too high. Figure 3b As shown, the battery has poor cycle performance, and the battery capacity decays significantly with the increase in the number of charge and discharge cycles.
[0250] In Comparative Example 1, the rebound of the negative electrode sheet is reduced, but because the active material layer does not include the first graphite layer, the lithium titanate layer is directly formed on the surface of the current collector, and the electronic conductivity of the negative electrode sheet is poor. Compared with Example 1, the rate performance of the lithium ion battery of Comparative Example 1 is poor, and the rate capacity retention rates Q1 and Q2 are significantly reduced.
[0251] In Comparative Example 2, the rebound of the negative electrode sheet is also reduced, but because the active material layer does not include the second graphite layer, a stable and dense SEI film cannot be formed on the surface of the active material layer, and lithium ions are continuously consumed during the charge and discharge process, and the capacity of the lithium-ion battery is easily attenuated. Figure 3b As shown in the figure, compared with Example 1, the capacity of the lithium ion battery of Comparative Example 2 decays more after undergoing charge and discharge cycles, and the cycle capacity retention rate P after 200 cycles is 200 Relatively low.
[0252] Examples 2 to 8 and Comparative Examples 3 to 4
[0253] The negative electrode sheets and lithium ion batteries of Examples 2 to 8 and Comparative Examples 3 to 4 were prepared by substantially the same method as in Example 1, except that the OI values of the first graphite and / or the second graphite used were respectively shown in Table 2. The OI values of the first graphite layer and the second graphite layer in the negative electrode sheets of Examples 2 to 8 and Comparative Examples 3 to 4 measured according to the method described above are also shown in Table 2.
[0254] By the test method described above, the rebound rate of the negative electrode sheets in Examples 2 to 8 and Comparative Examples 3 to 4 at different stages, the cycle expansion force and the corresponding expansion force growth rate of the lithium ion batteries in Examples 2 to 8 and Comparative Examples 3 to 4 after 200 cycles, and the cycle capacity retention rate P 200 The results are shown in Table 2 together with the rate capacity retention rates Q1 and Q2.
[0255] For the lithium ion batteries prepared in Example 2 and Comparative Examples 3 to 4, the curves of the cycle capacity retention rate versus the number of cycles are shown in FIG. Figure 4a In addition, the bar graph showing the rate capacity retention rate of the lithium ion batteries of Example 2 and Comparative Examples 3 to 4 is shown in FIG. Figure 4b shown.
[0256] Table 2
[0257]
[0258] It can be seen from the results of Table 1 and Table 2 that in Examples 1 to 8, the lithium titanate layer included in the active material layer can effectively suppress the rebound of the negative electrode sheet. At the same time, since the OI value of the first graphite layer disposed on the surface of the current collector is greater than or equal to 20.0, this means that a relatively high proportion of (004) crystal planes parallel to the graphite sheet structure are exposed in the first graphite layer, which is conducive to the flow of electrons on the graphite surface and the transmission of electrons through the current collector, and the electronic conductivity of the negative electrode sheet is greatly increased, thereby fully ensuring the rate performance of the lithium-ion battery. In addition, since the OI value of the second graphite layer is less than 15.0, this means that a relatively high proportion of (110) crystal planes perpendicular to the graphite sheet structure are exposed in the second graphite layer, which is conducive to the embedding and extraction of lithium ions in graphite, and the lithium ion conduction rate of the negative electrode sheet is greatly increased. Moreover, a relatively high proportion of (110) crystal faces are exposed in the second graphite layer, which can form a denser and more stable SEI film on the interface when in contact with the electrolyte, thereby delaying the consumption of active lithium ions during the battery charge and discharge process and significantly reducing the battery capacity decay. In Examples 1 to 8, the cycle capacity retention rate P of the lithium-ion battery after 200 cycles is 200 It reached 88.6% or more, and the rate capacity retention rates Q1 and Q2 reached 84.0% or more and 76.0% or more, respectively.
[0259] In Comparative Examples 3 and 4, the OI value of the second graphite layer is large, which is beyond the scope of the present invention, which means that the proportion of the (110) crystal plane exposed in the second graphite layer is reduced, while the proportion of the (004) crystal plane is increased, which is not conducive to the insertion and extraction of lithium ions, and the density of the SEI film formed when in contact with the electrolyte is reduced. As a result, Figure 4aAs shown in the figure, compared with Example 2, the capacity of the lithium ion batteries of Comparative Examples 3 and Comparative Examples 4 decays more after undergoing charge and discharge cycles, and the cycle capacity retention rate P after 200 cycles is 200 Significantly lower. In addition, Figure 4b As shown, compared with Example 2, the rate capacity retention rates Q1 and Q2 of the lithium ion batteries of Comparative Examples 3 and 4 under 1C and 2C conditions are significantly reduced.
[0260] Embodiments 9-10
[0261] The negative electrode sheets and lithium ion batteries of Examples 9 to 10 were prepared by substantially the same method as in Example 1, except that the OI values of the first graphite and / or the second graphite used were respectively as shown in Table 3. The OI values of the first graphite layer and the second graphite layer in the negative electrode sheets of Examples 9 to 10 measured according to the method described above are also shown in Table 3.
[0262] Table 3
[0263]
[0264] The rebound rate of the negative electrode sheets in Examples 9 to 10 at different stages, the expansion force growth rate of the lithium-ion batteries in Examples 9 to 10 after 200 cycles, and the cycle capacity retention rate P were measured by the test method described above. 200 The results are shown in Table 3 together with the rate capacity retention rates Q1 and Q2.
[0265] In Examples 9 to 10, the OI value of the second graphite layer is within the preferred range of 8 to 12 of the present invention. From the results of Tables 2 and 3, it can be seen that compared with Examples 3 to 5, when the OI value of the second graphite layer is within the preferred range, the cycle performance and rate performance of the lithium ion battery can be better balanced.
[0266] Examples 11-12
[0267] The negative electrode sheets and lithium-ion batteries of Examples 11 to 12 were prepared by a method substantially the same as that of Example 1, except that, during the preparation of the negative electrode sheets, the coating amount of the slurry was adjusted so that the thicknesses of the first graphite layer, the lithium titanate layer, and the second graphite layer in the negative electrode sheets of Examples 11 to 12 after the cold pressing process were as shown in Table 4.
[0268] Table 4
[0269]
[0270] The rebound rate of the negative electrode sheets in Examples 11 to 12 at different stages, the expansion force growth rate of the lithium-ion batteries in Examples 11 to 12 after 200 cycles, and the cycle capacity retention rate P were measured by the test method described above. 200 The results are shown in Table 4 together with the rate capacity retention rates Q1 and Q2.
[0271] It can be seen from the results in Table 1 and Table 4 that, compared with Examples 11 and 12, in Example 1, the thickness of the lithium titanate layer is within the preferred range of 25 to 50 μm of the present invention, which can ensure that the lithium titanate layer can fully exert the effect of suppressing the rebound of the negative electrode sheet while maintaining the cycle performance and rate performance of the lithium-ion battery.
[0272] Embodiments 13-14
[0273] The negative electrode sheets and lithium-ion batteries of Examples 13 to 14 were prepared by a method substantially the same as that of Example 1, except that, during the preparation of the negative electrode sheets, the coating amount of the slurry was adjusted so that the compaction density of the negative electrode sheets of Examples 13 to 14 was as shown in Table 4.
[0274] The rebound rate of the negative electrode sheets in Examples 13 to 14 at different stages, the expansion force growth rate of the lithium-ion batteries in Examples 13 to 14 after 200 cycles, and the cycle capacity retention rate P were measured by the test method described above. 200 The results are shown in Table 4 together with the rate capacity retention rates Q1 and Q2.
[0275] In Examples 1 and 13, the compaction density of the negative electrode sheet is within the preferred range of 0.9 to 1.8 g / cm 3 From the results of Table 1 and Table 4, it can be seen that compared with Example 14, the electrolyte wetting ability of the negative electrode plate is fully guaranteed, thereby further ensuring the rate performance of the battery. In addition, the compaction density of the negative electrode plate is within the above-mentioned limited range of the present invention, which can further reduce the rebound of the negative electrode plate during the manufacturing process of the lithium-ion battery and the charge and discharge cycle process.
[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode sheet, comprising a current collector and an active material layer disposed on at least one surface of the current collector, characterized in that: The active material layer comprises: First graphite layer; a lithium titanate layer; and The second graphite layer, The first graphite layer is disposed on at least one surface of the current collector, the lithium titanate layer is disposed on a surface of the first graphite layer, the second graphite layer is disposed on a surface of the lithium titanate layer, and The OI value of the first graphite layer is greater than or equal to 20.0, and the OI value of the second graphite layer is less than or equal to 15.
0.
2. The negative electrode sheet according to claim 1, characterized in that: The OI value of the first graphite layer is 30.0-40.
0.
3. The negative electrode sheet according to claim 1, characterized in that: The OI value of the second graphite layer is 8.0-12.
0.
4. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first graphite layer is less than or equal to 100 μm.
5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the lithium titanate layer is 25-50 μm.
6. The negative electrode sheet according to claim 1, characterized in that: The thickness of the second graphite layer is less than or equal to 100 μm.
7. The negative electrode sheet according to claim 1, characterized in that: The active material layer has a thickness of 50 to 150 μm.
8. The negative electrode sheet according to claim 1, characterized in that: The compaction density of the negative electrode sheet is 0.9 to 1.8 g / cm 3 .
9. A method for preparing a negative electrode sheet, characterized in that: include: providing a current collector; forming a first graphite layer including a first graphite on at least one surface of the current collector; forming a lithium titanate layer including lithium titanate on a surface of the first graphite layer; forming a second graphite layer including a second graphite on the surface of the lithium titanate layer to obtain a laminate having an active material layer on at least one surface of the current collector, wherein the active material layer includes the first graphite layer, the lithium titanate layer and the second graphite layer; and Cold pressing the laminate to obtain the negative electrode sheet; The OI value of the first graphite is greater than 2.0 and less than or equal to 6.0, and the OI value of the second graphite is greater than or equal to 0.5 and less than 2.
0.
10. The preparation method according to claim 9, characterized in that: The OI value of the first graphite is 3.0-5.
0.
11. The preparation method according to claim 9, characterized in that: The OI value of the second graphite is 1.0-1.
5.
12. The preparation method according to claim 9, characterized in that: The cold pressing pressure is 15-70T.
13. The preparation method according to claim 9, characterized in that: After the stack is cold pressed, the OI value of the formed first graphite layer is greater than or equal to 20.0, and the OI value of the formed second graphite layer is less than or equal to 15.
0.
14. The preparation method according to claim 9, characterized in that: After the stacked body is cold-pressed, the OI value of the formed first graphite layer is 30.0 to 40.
0.
15. The preparation method according to claim 9, characterized in that: After the stacked body is cold-pressed, the OI value of the formed second graphite layer is 8.0 to 12.
0.
16. The preparation method according to claim 9, characterized in that: After the stack is cold pressed, the compaction density of the negative electrode sheet formed is 0.9 to 1.8 g / cm 3 .
17. A secondary battery, characterized in that: include: Positive electrode; A negative electrode sheet according to any one of claims 1 to 8, or a negative electrode sheet prepared by the preparation method according to any one of claims 9 to 16; Electrolytes; and Diaphragm.
18. A battery module, characterized in that: Includes the secondary battery as claimed in claim 17.
19. A battery pack, characterized in that: Comprising the battery module as claimed in claim 18.
20. An electrical device, characterized in that: Includes the secondary battery according to claim 17, the battery module according to claim 18, or the battery pack according to claim 19.
Citation Information
Patent Citations
Pulp for lithium ionic cell electrode and manufacturing method thereof
CN101393978A
Lithium ion battery negative electrode, preparation method thereof and lithium ion battery
CN112670445A